Women's work : the first 20,000 years : women, cloth, and society in early times - Barber, E. J. W., 1940-
New discoveries about the textile arts reveal women's unexpectedly influential role in ancient societies. Barber "weaves the strands of mythology and literature, archaeology,ethnology, and documented history into a richtapestry" says John Noble Wilford, New York Times Book Review. Photos and drawings. Author lectures.